Movida de piso - Gastañaduy, Alfonso (2004)
Cometa Ltd., a small company of distribution of products for welding located in Huancayo, manages to position itself advantageously in the market for some years selling mainly to mining centers, while its competitors limited their operations to the city of Huancayo. The best-selling product is the electrode from the Trikón factory, which no other company distributes in the center of the country. The problems begin when the owners of Cometa find out that their main competitor in Huancayo, which years ago had stopped selling Trikon products due to a serious conflict with this manufacturer, will distribute this product again.